Analysis of teaching and learning of chemical transformations in national publications (Research, Society and Development, 2019)
The objective of this research is to present an analysis carried out in the annals of the National Chemistry Teaching Meeting (ENEQ) and in the editions of the Journal Química Nova na Escola (QNEsc), between 2008 and 2018, on the topic of chemical transformations. For the analysis, a bibliographic research was carried out in the annals and in the editions of the journal in order to detect how has been occurring the teaching and learning of the topic of chemical transformations in Basic and Higher Education. The bibliographic research was carried out in four stages: 1) Selection of the annals and editions of the journal QNEsc for study; 2) Data collection through the collection of complete papers, abstracts and articles that address the topic of chemical transformations; 3) Selection of the complete papers, abstracts and articles from their full reading, and elimination of those that had no relation with the topic researched; 4) Analysis of the complete papers, abstracts and articles selected from three dimensions. Of the total, 82 publications were found in the sources investigated and the results indicate that: the number of publications found was not expressive, because of a total of 5,169 publications, only 6.49% corresponded to the subject investigated; most of the publications are empirical, with a qualitative approach, centered on the macroscopic aspects of the chemical transformations and are destined to Basic Education; the theoretical basis most used by the authors was the theory on chemical transformations, with emphasis on specific contents related to the researched subject; the main results of the researches present differentiated teaching proposals, since most of the publications presented activities with this bias in the classroom, in this manuscript we will describe some and their main contributions. By means of the study carried out, it is concluded that the number of publications on this subject is still insufficient, and it is necessary to carry out more research on the topic of chemical transformations, mainly considering the three levels of representation of matter.